Translation and cultural adaptation of the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) pain scale into Arabic for use with patients with diabetes in Libya. Issue 1 (1st January 2017) - Garoushi, Sabri; Johnson, Mark I.; Tashani, Osama A.
ABSTRACT: In Libya neuropathic pain is rarely assessed in patients with diabetes. The Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) pain scale is used worldwide to screen for neuropathic pain. There is no Arabic version of LANSS for use in Libya. The aim of this study was to develop an Arabic version of LANSS and to assess its validity and reliability in diabetic patients in Benghazi, Libya. LANSS was translated into Arabic by four bilingual translators and back translated to English by a university academic. Validity and reliability of the Arabic LANSS was assessed on 110 patients attending a Diabetes Centre in Benghazi. Concurrent validity was tested and compared with the Self-completed Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS). Test-retest reliability was conducted 1–2 weeks later. Internal consistency and inter-class correlation (ICC) between LANSS and S-LANSS was also tested. Internal consistency within first completion of the Arabic LANSS was acceptable (Cronbach's alpha = 0.793) and similar to the Arabic S-LANSS (0.796) and the second completion of the Arabic LANSS (0.795). ICC between the Arabic LANSS and the Arabic S-LANSS was 0.999 ( p  < 0.001). Test-retest reliability (ICC) between first and second completions of the Arabic LANSS was 0.999 ( p  < 0.001). Kappa measurement of agreement between the two Arabic LANSS completions and S-LANSS was high on all seven items (Kappa >0.95, p  < 0.0001). We concluded that the Arabic version of LANSS pain scale was valid and reliable for use on Libyan diabetic patients. This study provided results suggesting that the S-LANSS could also be used on diabetic patients.